Quantitative analysis of CDX2 protein expression improves its clinical utility as a prognostic biomarker in stage II and III colon cancer. (February 2021) - den Uil, Sjoerd H.; de Wit, Meike; Slebos, Robbert J.C.; Delis-van Diemen, Pien M.; Sanders, Joyce; Piersma, Sander R.; Pham, Thang V.; Coupé, Veerle M.H.; Bril, Herman; Stockmann, Hein B.A.C.; Jimenez, Connie R.; Meijer, Gerrit A.; et al.
Abstract: Aim: Better stratification of patients with stage II and stage III colon cancer for risk of recurrence is urgently needed. The present study aimed to validate the prognostic value of CDX2 protein expression in colon cancer tissue by routine immunohistochemistry and to evaluate its performance in a head-to-head comparison with tandem mass spectrometry–based proteomics. Patient and methods: CDX2 protein expression was evaluated in 386 stage II and III primary colon cancers by immunohistochemical staining of tissue microarrays and by liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis using formalin-fixed paraffin-embedded tissue sections of a matched subset of 23 recurrent and 23 non-recurrent colon cancers. Association between CDX2 expression and disease-specific survival (DSS) was investigated. Results: Low levels of CDX2 protein expression in stage II and III colon cancer as determined by immunohistochemistry was associated with poor DSS (hazard ratio [HR] = 1.97 (95% confidence interval [CI]: 1.26–3.06); p = 0.002). Based on analysis of a selected sample subset, CDX2 prognostic value was more pronounced when detected by LC-MS/MS (HR = 7.56 (95% CI: 2.49–22.95); p < 0.001) compared to detection by immunohistochemistry (HR = 1.60 (95% CI: 0.61–4.22); p = 0.34). Conclusion: This study validated CDX2 protein expression as a prognostic biomarker in stage II and III colon cancer, conform previous publications. CDX2 prognostic value appeared to be underestimated when detected by routine immunohistochemistry, probably due to the semiquantitative and subjective nature of this methodology. Quantitative analysis of CDX2 substantially improved its clinical utility as a prognostic biomarker. Therefore, development of routinely applicable quantitative assays for CDX2 expression is needed to facilitate its clinical implementation. Highlights: CDX2 is a prognostic biomarker for patients with stage II and III colon cancer. CDX2 testing by mass spectrometry outperformed routine immunohistochemistry. Application of quantitative assays can improve clinical utility of biomarkers.